2016
DOI: 10.3390/antibiotics5030024
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Antibiotics: Contemporary Challenges

Abstract: Most ribosomal antibiotics obstruct distinct ribosomal functions. In selected cases, in addition to paralyzing vital ribosomal tasks, some ribosomal antibiotics are involved in cellular regulation. Owing to the global rapid increase in the appearance of multi-drug resistance in pathogenic bacterial strains, and to the extremely slow progress in developing new antibiotics worldwide, it seems that, in addition to the traditional attempts at improving current antibiotics and the intensive screening for additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…In the current study, mutations in L4 and L22 were associated with elevated MICs for GAM, TYLT, TIP, and TIL. Given that these ribosomal proteins form the narrowest constriction of the protein exit tunnel [52], with both having loops that extend adjacent to macrolide binding sites [53], the presence of mutations is consistent with the AST phenotypes. All isolates (n = 126) also had mutations in L22 relative to the type strain, a result more prevalent than reported by Lerner et al [31], where the nonsynonymous mutation Gln90His (E. coli numbering) in L22 was observed in 75% of isolates.…”
Section: Discussionmentioning
confidence: 70%
“…In the current study, mutations in L4 and L22 were associated with elevated MICs for GAM, TYLT, TIP, and TIL. Given that these ribosomal proteins form the narrowest constriction of the protein exit tunnel [52], with both having loops that extend adjacent to macrolide binding sites [53], the presence of mutations is consistent with the AST phenotypes. All isolates (n = 126) also had mutations in L22 relative to the type strain, a result more prevalent than reported by Lerner et al [31], where the nonsynonymous mutation Gln90His (E. coli numbering) in L22 was observed in 75% of isolates.…”
Section: Discussionmentioning
confidence: 70%
“…and the resistance to them have been critically described in several recent comprehensive reviews (84,89,(95)(96)(97)(98)(99)(100)(101)(102)(103), in this article we relate mainly to species specificity in susceptibility to antimicrobial drugs of multidrug-resistant bacteria alongside vicious parasites. We elaborate on directions that could be suitable for the design and the creation of future antimicrobial therapeutics with better distinction between pathogens and useful bacterial species in the microbiome, on ecological aspects of antibiotic resistance, and on the pros and cons of species-specific drugs.…”
Section: Figurementioning
confidence: 99%
“…Among them is a reasonable large space at the rims of the erythromycin binding pockets of both pathogenic bacteria, due to the length of the chain of protein rpL32 of the S. aureus and E. coli ribosome (shorter compared with its length in the other ribosomes) (47,103). This special arrangement provides space for extending erythromycin in a fashion that should allow binding specifically to the pathogenic species studied so far, namely S. aureus and E. coli, and not to many nonpathogens, represented by D. radiodurans and T. thermophilus (Figure 2).…”
Section: Better Discrimination and Specificitymentioning
confidence: 99%
“…Structural analyses of bacterial ribosome particles in complex with paralyzing antibiotics shed light on their mode of action and basis of selectivity, thus elucidating clinical efficacy. These studies have revealed that clinical antibiotics target select functional sites in the ribosome, including the decoding region, the peptidyl transferase center (PTC), the nascent chain exit tunnel, the inter-subunit bridges and the tRNA accommodation corridor ( 3 ). These efforts have also illuminated diverse resistance mechanisms that have evolved in human pathogens to evade various antibiotic agents ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%